Variation of iron in groundwater and its impact on human health in Dhangadhi area, Far-Western Nepal - Upadhyaya, Nikita; Rijal, Moti Lal (Journal of Nepal Geological Society, 2025)
In April 2024, a study was conducted to assess the distribution of iron in the several types of groundwater resources in the Dhangadhi area. A total of 50 samples were collected, including 29 from shallow sources and 21 from deep sources. Iron was detected in 24 shallow and 8 deep sources. In shallow sources, iron concentrations ranged from 0.17 to 9.68 mg/l, with a mean of 2.46 mg/l and a standard deviation of 2.14 mg/l, while in deep sources, concentrations ranged from 0.17 to 7.14 mg/l, with a mean of 1.30 mg/l and a standard deviation of 2.24 mg/l. Except for samples SS5, SS7, DS10, and DS15 all other samples exceeded the permissible iron limit of 0.3 mg/l set by NDWQS 2022. The Water Quality Index (WQI), without considering iron, ranged from 2.10 to 122.22, classifying groundwater as 52% excellent, 34% good, 6% very poor, and 8% unsuitable for drinking. WQI ranged from 1.985 to 446.70, when iron was included, categorizing groundwater as 38% excellent, 20% good, 6% poor, 6% very poor, and 30% unsuitable for drinking, highlighting iron as the primary factor degrading water quality. The highest concentration was found in sample SS2 in the northern part of the area, with industrial and agricultural activities contributing to elevated levels. The reliance on shallow sources with high iron concentrations has led to public health issues, including liver and kidney diseases. Effective management and stringent quality control measures are essential to protect this critical water resource.